METHOD FOR FORMING THE REQUIRED QUANTITY OF SPARE PARTS FOR TRANSPORT MEANS REPAIR - Poliakov, Andriy; Galuschak, Dmitro; Galuschak, Oleksandr; Antoniuk, Oleg (Scientific Works of Vinnytsia National Technical University, 2015)
An algorithm is presented for realization of the method for forming the required quantity of spare parts for transport means repair. The analysis of factors influencing the demand of a motor transport enterprise for spare parts in the process of hauling stock operation has been conducted. REFERENCES 1. Шрайбфедер Джон. Эффективное управление запасами / Джон Шрайбфедер; пер. с англ. – 2-ое изд. – М.: Альпина Бизнес Букс, 2006. – 304 с. 2. Бродецкий Г. Л. Управление запасами : учеб. пособие / Г. Л. Бродецкий. – М.: Эксмо, 2008. – 352 с. 3. Лукинский В. С. Логистика автомобильного транспорта: Учеб. пособие / В. С. Лукинский, В. И. Бережной, Е. В. Бережная и др. – М. : Финансы и статистика, 2004. – 368 с. 4. Радионов А. Р. Логистика: Нормирование сбытовых запасов и оборотных средств предприятия: Учеб пособие / А. Р. Радионов, Р. А. Радионов. – М.: Дело, 2002. – 416 с. 5. Стерлигова А. Н. Управление запасами у цепях поставок: Учебник / А. Н. Стерлигова. – М.: ИНФРА-м, 2008. – 430 с. 6. Майзнер Н. А. Складская логистика / Н. А. Майзнер, М. Ю. Николаева. – ТГЭУ. 2006. – 88 с.